2009
DOI: 10.1016/j.virol.2008.10.042
|View full text |Cite
|
Sign up to set email alerts
|

A virulent isolate of yellow head nidovirus contains a deformed envelope glycoprotein gp116

Abstract: Yellow head virus (YHV) is a highly virulent pathogen of penaeid shrimp. An isolate obtained from Penaeus vannamei during a yellow head disease outbreak in February 2006 in Ratchaburi Province, Thailand was purified following passage in experimentally infected shrimp. SDS-PAGE of purified virions indicated that envelope glycoprotein gp116 in the Ratchaburi/2006 isolate was smaller and relatively less abundant than in the Chachoengsao/1998 YHV reference strain. The variant gp116 reacted poorly in immunoblots wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…Most sequence diversity, including block insertions/deletions, occurs near to the gp116 N terminus, generated by cleavage at a signal peptidase type 1 site at TM domain 3 of the ORF3 polyprotein. Two YHV genotype 1 variants from Thailand, one virulent (genotype 1b) (Sittidilokratna et al, 2009) and the other non-virulent (A-YHV) (Gangnonngiw et al, 2009), for which sequence data have been reported recently, both possess a 54 aa deletion in the gp116 Nterminal region that eliminates the N 63 TS and N 44 ST sites, found here to be glycosylated in the YHV genotype 1a strain. Despite sequence differences and the loss of these two glycan-linked sites in gp116 of YHV genotype 1b strains, they retain virulence, albeit somewhat reduced compared with genotype 1a strains (Sittidilokratna et al, 2009).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Most sequence diversity, including block insertions/deletions, occurs near to the gp116 N terminus, generated by cleavage at a signal peptidase type 1 site at TM domain 3 of the ORF3 polyprotein. Two YHV genotype 1 variants from Thailand, one virulent (genotype 1b) (Sittidilokratna et al, 2009) and the other non-virulent (A-YHV) (Gangnonngiw et al, 2009), for which sequence data have been reported recently, both possess a 54 aa deletion in the gp116 Nterminal region that eliminates the N 63 TS and N 44 ST sites, found here to be glycosylated in the YHV genotype 1a strain. Despite sequence differences and the loss of these two glycan-linked sites in gp116 of YHV genotype 1b strains, they retain virulence, albeit somewhat reduced compared with genotype 1a strains (Sittidilokratna et al, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…Two YHV genotype 1 variants from Thailand, one virulent (genotype 1b) (Sittidilokratna et al, 2009) and the other non-virulent (A-YHV) (Gangnonngiw et al, 2009), for which sequence data have been reported recently, both possess a 54 aa deletion in the gp116 Nterminal region that eliminates the N 63 TS and N 44 ST sites, found here to be glycosylated in the YHV genotype 1a strain. Despite sequence differences and the loss of these two glycan-linked sites in gp116 of YHV genotype 1b strains, they retain virulence, albeit somewhat reduced compared with genotype 1a strains (Sittidilokratna et al, 2009). It has been postulated that sequence differences elsewhere, possibly in non-structural proteins, are important in conferring virulence of these two variants of YHV genotype 1 (Gangnonngiw et al, 2009).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…2). However, as reported previously, GAV is far less virulent than YHV for which the LD 50 is typically 10 8 -to 10 9 -fold lower in inocula containing equivalent viral genetic loads (Sittidilokratna et al, 2009a;Wijegoonawardane et al, 2009). Consequently, YHV lethal challenge experiments in which very effective RNAiinduced inhibition of infection was observed employed a virus dose~10 5 -fold lower than was possible for GAV (Yodmuang et al, 2006).…”
Section: Discussionmentioning
confidence: 84%
“…YHV3 in Thailand and Vietnam, YHV4 in India, YHV5 in Malaysia, Thailand and the Philippines, and YHV6 in Mozambique). YHV1 types occurring in Thailand have also been assigned to subtypes YHV1a and YHV1b based on the latter possessing a 54 amino acid deletion in the N-terminal region of the ORF3 coding sequence, although both genotypes retain similar virulence in P. vannamei (Sittidilokratna et al 2009, Senapin et al 2010.…”
Section: Introductionmentioning
confidence: 99%